Tanggung Jawab Sosial dan Lingkungan Perusahaan Penanaman Modal - Ahmad Fauzi (Universitas Muhammadiyah Sumatera Utara, 2020)
Corporate social responsibility is a corporate commitment to sustainable economic development in an effort to improve the quality of life and the environment. So that this commitment is not only the obligation to budget funds, but also how to care for the environment and the community as part of the strategic plan of each company's activities. Corporate social responsibility and environment are expected to not merely refer to the financial budget inputs provided, but include the appropriateness and fairness of the company's overall activities as a realization of its concern for the environment and society. This writing used descriptive analytical research methods complemented by literature and comparative studies, as well as normative juridical approaches. The results showed that corporate social and environmental responsibility (corporate social responsibility) must be carried out in partnership with the stakeholders followed by transparency and accountability and all parties.